2020
DOI: 10.3390/en13195018
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Solid Particle Sedimentation and Bed Formation Behaviors Using a Hybrid Method

Abstract: In the safety analysis of sodium-cooled fast reactors, numerical simulations of various thermal-hydraulic phenomena with multicomponent and multiphase flows in core disruptive accidents (CDAs) are regarded as particularly difficult. In the material relocation phase of CDAs, core debris settle down on a core support structure and/or an in-vessel retention device and form a debris bed. The bed’s shape is crucial for the subsequent relocation of the molten core and heat removal capability as well as re-criticalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…For sloshing motion with solid particles, taking into account the past numerical investigations into particle-related phenomena for the assessment of severe accidents in SFRs (Shamsuzzaman et al, 2014;Tagami and Tobita, 2014;Guo et al, 2017;Tagami et al, 2018;Sheikh et al, 2020), in which solid particles played a major role in the multiphase behaviors, microscopic models for inter-particle collisions and contacts or the discrete element method (DEM) may additionally be considered in the simulations to provide appropriate estimates of particle-particle interactions. 6) Further investigations into the effect of coupling between nuclear power deposition as well as recriticality and pool sloshing motion based on the knowledge obtained from thermal-hydraulics studies.…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…For sloshing motion with solid particles, taking into account the past numerical investigations into particle-related phenomena for the assessment of severe accidents in SFRs (Shamsuzzaman et al, 2014;Tagami and Tobita, 2014;Guo et al, 2017;Tagami et al, 2018;Sheikh et al, 2020), in which solid particles played a major role in the multiphase behaviors, microscopic models for inter-particle collisions and contacts or the discrete element method (DEM) may additionally be considered in the simulations to provide appropriate estimates of particle-particle interactions. 6) Further investigations into the effect of coupling between nuclear power deposition as well as recriticality and pool sloshing motion based on the knowledge obtained from thermal-hydraulics studies.…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…In IGCAR, experiments were conducted with high-density lead particles to develop an empirical model for predicting the repose angle of the formed debris bed [65]. At Kyushu University and JAEA, by employing single (i.e., single-sized and single-shaped) solid particles and mixed solid particles, some typical experimental parametric impacts on the overall accumulated-bed characteristics (e.g., bed height and shape) were clarified [23,28,29,[62][63][64]. From their experiments, it was confirmed that under different experimental parameters, the debris bed's geometrical shape would generally be convex or concave.…”
Section: Investigations Focusing On Overall Accumulated-bed Character...mentioning
confidence: 99%
“…Therefore, to elucidate the characteristics and mechanisms of DBF behavior in the case of an SFR, in the past decade, extensive experimental and modeling studies were performed separately at Kyushu University, the Japan Atomic Energy Agency (JAEA) [23,28,29,[62][63][64], Indira Gandhi Centre for Atomic Research (IGCAR) [65], and Sun Yat-Sen University (SYSU) [24,[66][67][68][69][70][71][72]. Figure 2 summarizes these investigations, which can be divided according to their different focal points: (1) investigations focusing on the overall accumulated-bed characteristics; and (2) investigations focusing on the flow regime characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations